DETERMINANTS OF PHYSICAL DEVELOPMENT IN ATHLETES: RISK FACTORS AND CHALLENGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
That is why all-round mature, healthy and mature upbringing of the younger generation is in the ashes of pedagogues, educators, medical staff, parents. Physical development is an important indicator of the health of a growing organism and has two meanings: the first describes the maturation, formation and biological age of the organism, and the second classifies the morpho-functional state at any time.